A humanização em saúde no ensino odontológico no Brasil - Rafaela Reis da Silva (2022)
The objective of this study was to evaluate the insertion and development of the Humanization theme in the Political Pedagogical Project of public and private legal institutions that offer the Dentistry course in Brazil. The reason for this research was born from the results obtained from my master's research carried out at the Universidade Federal de Minas Gerais. The findings of this study showed that the humanization approach in dental education is sometimes deficient, which leads to the lack and practice of reflection on humanization in health care. Therefore, it is necessary to carry out a curricular evaluation of the dentistry courses in the country to identify how the topic is worked on during training in a transversal way. This study used a qualitative descriptive and exploratory method with a documentary corpus (n=100 projects). Three surveys were carried out in the e-MEC Registry to survey the number of Dentistry courses offered in Brazil. The theoretical frameworks for the elaboration of the analytical matrix for data extraction were: ´´National Curriculum Guidelines for the undergraduate course in Dentistry´´ and ´´Guidelines of the National Humanization Policy´´. In order to explore the documentary corpus, the analytical matrix was used to extract primary data, divided into three themes: Subject of care; Organization and management of care; and Right to health. Within each theme, their respective categories: Reception and shared extended clinic; Ambience and participatory management and co-management; User rights and defense. To analyze the findings, a document analysis was performed based on content analysis. The work of developing the humanistic profile of the graduate has to be transversal. Thus, an innovative curriculum is considered to be one whose educational proposal seeks to overcome, between theory and practice, the fragmentation of disciplines in the teaching-learning process.